The effects of submaximal exercise training on cardiovascular functions and physical capacity in dogs with myxomatous mitral valve disease - Saikaew Sutayatram (2018)
© 2018 Chulalongkorn University Printing House. All rights reserved. Myxomatous mitral valve disease (MMVD), an important disease in senile small breed dogs, leads to deterioration of cardiovascular function and impairment of functional capacity resulting in poor quality of life. Submaximal treadmill running has been used as both cardiovascular training and testing worldwide in humans and recently in animals. The objectives of this study were to examine the effects of submaximal endurance training (ET) by treadmill running on safety, adverse events, cardiovascular adaptations, hematology, functional capacity, and the feasibility of submaximal treadmill running test and 6-minute walk test (6-MWT) in dogs with MMVD. Six adult beagle dogs with MMVD, stage B1 according to the American College of Veterinary Internal Medicine (ACVIM) guideline, were examined before the study, at weeks 4 and 8 of the ET. The cardiovascular functions assessed by echocardiography and electrocardiography, systolic blood pressure, hematology and blood chemistry profiles, and functional capacity were determined. All dogs completed all tests and ET sessions without clinical complication. ET resulted in significant improvement in physical capacity measured by submaximal treadmill running test and 6-MWT, while cardiac function parameters were not altered. Moreover, serum creatinine was significantly decreased. In conclusion, ET and submaximal exercise tests are clinically feasible. The ET can improve physical capacity in dogs with MMVD, stage B1. Therefore, supervised moderate ET and submaximal exercise tests should be incorporated in MMVD management.